2014
DOI: 10.1038/emm.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

CYP19 gene variant confers susceptibility to endometriosis-associated infertility in Chinese women

Abstract: An aromatase encoded by the CYP19 gene catalyzes the final step in the biosynthesis of estrogens, which is related to endometriosis development. To assess the association of CYP19 gene polymorphisms with the risks of endometriosis, chocolate cysts and endometriosis-related infertility, a case–control study was conducted in Chinese Han women by recruiting 225 healthy control females, 146 patients with endometriosis, 94 endometriosis women with chocolate cyst and 65 women with infertility resulting from endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…The overall risk of either disease outcome was not related to any of the individual genotypes or block-specific haplotypes although the risk of breast cancer correlated with several gene variants differed according to proliferation status. The observed [15]. Moreover, another study by Chen et al (2008) found that the elevated hazard of breast cancer with proliferative fibrocystic status about individual CYP19A1 markers was pronounced among women who were post-menopausal or had a BMI ≥23 kg/m 2 .…”
Section: Discussionmentioning
confidence: 83%
“…The overall risk of either disease outcome was not related to any of the individual genotypes or block-specific haplotypes although the risk of breast cancer correlated with several gene variants differed according to proliferation status. The observed [15]. Moreover, another study by Chen et al (2008) found that the elevated hazard of breast cancer with proliferative fibrocystic status about individual CYP19A1 markers was pronounced among women who were post-menopausal or had a BMI ≥23 kg/m 2 .…”
Section: Discussionmentioning
confidence: 83%
“…CYP19A1 gene polymorphism is associated with reduced aromatase activity, which can lead to the development of endometriosis (Wang et al, 2010;Zaree et al, 2015;Hosseini et al, 2016;Abu Hashim, 2016). While previous studies have investigated the association between CYP19A1 and risk of endometriosis, the results were inconsistent (Hur et al, 2007;Vietri et al, 2009;Yang et al, 2010;Szczepańska et al, 2013;Wang et al, 2012Wang et al, , 2014. We have shown that there is a significant correlation between CYP19A1 rs2899470 and risk of endometriosis in a Chinese population.…”
Section: Discussionmentioning
confidence: 68%
“…CYP450 is a member of the CYP superfamily, and its gene is located on chromosome 15q22 to q24. Two studies have previously reported that CYP19A1 polymorphism contributes to the pathogenesis of endometriosis (Szczepańska et al, 2013;Wang et al, 2014). It has been shown that glutathione S-transferases (GSTs) are involved in estrogen metabolism, and play an important role in endometriosis development (Kubiszeski et al, 2015;Henidi et al, 2015); polymorphisms in GST-encoding genes could influence the expression and function of CYP450.…”
Section: Introductionmentioning
confidence: 99%
“…The human enzyme CYP19 (cytochrome P450 aromatase, family 19), which is encoded by the CYP19 gene, is associated with circulating oestrogen levels. The polymorphism T>C (Trp/Arg) in codon 39 (rs2236722) of the CYP19 gene may alter aromatase activity and steroid hormone levels …”
Section: Frequency Of the Cyp17 Msp Ai (T>c) And Cyp19 T>c Genotypes mentioning
confidence: 99%